Identification of drought and heat tolerant tepary beans in a multi‐environment trial study - Barrera, Santos; Berny Mier y Teran, Jorge C.; Aparicio, Johan; Diaz, Jairo; Leon, Rommel; Beebe, Stephen; Urrea, Carlos A.; Gepts, Paul (Wiley, 2024)
Abiotic constraints, such as drought and heat driven by climate change, negatively impact the production of the common bean ( Phaseolus vulgaris L.), an essential grain legume worldwide. The ability to tolerate drought and heat stress in common bean can be improved by introducing genetic variation from related species, such as tepary bean ( Phaseolus acutifolius A. Gray), which has recently gained attention because of its adaptation to drought and heat stresses and potential use as a genetic resource and alternative crop. To better understand the phenotypic response of tepary bean to drought and heat stress in multiple environments and trials and to select highly adapted tepary beans, we conducted two field experiments. In Experiment 1, we compared the adaptation to drought stress of tepary bean ( n = 10), common bean ( n = 10), and Lima bean ( Phaseolus lunatus L.; n = 9) by assessing the reduction in grain yield under terminal drought compared to well‐irrigated conditions in two California locations with arid summer conditions. Of the three species, tepary bean showed the statistically strongest adaptation to terminal drought, followed by Lima bean and common bean. In Experiment 2, we evaluated a set of 22 tepary beans from contrasting origins for drought and heat stresses across multi‐environment trials (METs) in California, Nebraska, and Colombia, with common bean as a control. We found a considerable variation in the tepary bean phenotypic response to these MET conditions, as a result of a strong genotype × environment interaction. Also, we identified tepary bean accessions adapted to drought, heat, and well‐irrigated conditions across multiple climate zones. Understanding the performance of tepary bean across multiple environments and identifying tepary beans with broad and target‐specific adaptation will maximize the potential use of the species.